Cytotoxicity effect of Thymoquinone-loaded nanostructured lipid carrier (TQ-NLC) on liver cancer cell integrated with hepatitis B genome, Hep3B - Haron, Aminah Suhaila; Syed Alwi, Sharifah Sakinah; Saiful Yazan, Latifah; Abd Razak, Rohaina; Ong, Yong Sze; Zakarial Ansar, Fatin Hannani; Alexander, Henna Roshini (Hindawi, 2018)
Thymoquinone (TQ), a bioactive compound found in Nigella sativa, cannot be orally consumed due to its lipophilicity. In order to overcome this low bioavailability, TQ is loaded into a colloidal drug carrier known as a nanostructured lipid carrier (NLC). This study aims to determine the antiproliferative effects of TQ and TQ-NLC on liver cancer cells integrated with the hepatitis B genome, Hep3B. The Hep3B was treated with TQ or TQ-NLC for 24, 48, and 72 hours via MTT assay. The results confirm that TQ or TQ-NLC inhibited the growth of Hep3B at IC50 <16.7 μM for 72 hours. TQ was also found to induce cell cycle arrest at the G1 checkpoint while TQ-NLC induced non-phase-specific cell cycle arrest. Further analysis using Annexin V staining confirmed the apoptotic induction of TQ or TQ-NLC via activation of caspases-3/7. In ROS management, TQ acted as a prooxidant (increased the level of ROS), while TQ-NLC acted as an antioxidant (reduced the level of ROS). Molecular analysis demonstrated that the GSH system and the Nrf2/Keap1 signaling pathway in Hep3B influenced the differential responses of the cells towards TQ or TQ-NLC. Hence, this study demonstrated that TQ and TQ-NLC have in vitro anticancer effects on the Hep3B.